UNDERPRICING: INFORMASI AKUNTANSI DAN NON AKUNTANSI DALAM INITIAL PUBLIC OFFERING (IPO) - Risal Risal (Akuntabilitas, 2014)
The aim of this research was to test and to analyze some factors which influenceunderpricing phenomenon represented by accountancy information (ROA, TATO, CR, DERand firm size) and by non-accountancy information (auditor reputation, underwriterreputation, firm age and percentage of public offering). The population of the research was 103companies which from 2008 until 2012. Samples were collected by using purposive sampling.Multiple Regression model were used to test the relation between independent variables anddependent variables. Regression analysis shows that only underwriter reputation has negativeand significant influence on the level of underpricing. The accountancy information (ROA,TATO, CR, DER and firm size) and the non-accountancy information (auditor reputation,firm age and Percentage of Public Offering) do not have significant influence on underpricing.This study contributes theorically and practically to the influence of non-accountancyinformation on share prices during IPODOI: 10.15408/akt.v7i1.2645